Restoration of a Historic Building in Order to Improve Energy Efficiency and Energy Saving—Case Study—The Dining Room within the Žiča Monastery Property - Sekularac, N., Ivanović-Sekularac, J., Petrovski, A., Macut, N. and Radojevic, M. (Multidisciplinary Digital Publishing Institute, 2020)
A proper systematic approach to the restoration of historic buildings is crucial in the preservation of heritage buildings. This paper presents the unity between the restoration of a historic building and sustainability. The aim of the research is to establish an e ective method for the restoration of historic buildings and their reuse and sustainable renovation in terms of energy e ciency, in accordance with modern needs and conservation requirements while maintaining the authentic appearance. The main method in the paper is the observation of a historic building during its restoration and exploitation, analysis and evaluation of the results achieved in improving energy e ciency and energy saving in the example of the building within the Žica Monastery in Serbia, a cultural monument of exceptional importance. The subject of the research is the Dining Room within the Žiˇca Monastery and the analysis of the restoration results in order to ensure energy refurbishment and cultural heritage enhancement. The research findings are recommendations for the restoration and adaptive re-use of historic buildings, in accordance with modern requirements for comfort and environmental protection. The greatest contribution of this paper is the practical verification of energy refurbishment of the restored historic building, the Dining Room, by applying the principles and measures of energy e ciency, maintaining the authentic appearance of the building, in accordance with the conservation requirements.
Keywords: heritage conservation; energy refurbishment of historic buildings; cultural heritage; conservation requirements; sustainability